Atmospheric mercury uptake to foliage using in situ and transplanted lichens at the New Almaden Mining District, California, United States - Weiss-Penzias, Peter; Straw, Brittney; Rothman, Michelle; Zheng, Belle; Seelos, Mark; Rivas Meraz, Edwin; O’Day, Peggy A. (Frontiers in Environmental Chemistry, 2025)
Contaminated soils at former mercury (Hg) mines release Hg into the atmosphere that can be absorbed by the surrounding foliage and potentially contribute to inputs of Hg to downstream reservoirs and the food chain. Information on Hg re-emissions and atmospheric transport at the New Almaden Mining District (NAMD) in California’s Coast Range is lacking, despite the wealth of previous research at the site. This study addressed knowledge gaps regarding the locations of the highest Hg re-emissions using in-situ and transplanted lichens. High total Hg (THg) concentrations in lichen (up to 20 μg g−1) were found where ore-processing occurred pre-1900 and where the largest mines were. Mean background concentration of THg in lichen (156.3 ± 48.2 ng g−1) was observed >7.8 km away from the most contaminated site. Lichen THg was significantly higher than the background by 93–171 ng g−1 at locations along the shorelines of three small reservoirs in the NAMD. By transplanting lichens from background areas to three sites in the NAMD, statistically significant first-order rate constants of Hg uptake (0.0011–0.0036 days−1) were found. The trend in uptake rate constants matched the trend in THg concentrations in non-transplanted lichen and atmospheric concentrations monitored by Hg passive samplers. There was no trend in the control transplants nor in release rates. Speciation analysis of lichen samples collected from sites of highest contamination using Hg High Energy Resolution Fluorescence Detection (HERFD) XANES showed the dominance of α-HgS (cinnabar) in spectra, likely present as nanoparticles, in addition to variable Hg coordination by dithiol, sulfide, and chloride ligands at the micrometer scale. These results indicate that the majority of Hg in lichen is associated with non-volatile phases and/or organic species and suggest that a relatively small fraction of Hg exchanges with the atmosphere, in agreement with relatively low uptake rates. Overall, study results show that THg concentrations in lichen surveys have merit across gradients of contamination and indicate that Hg deposited to lichens is likely sequestered for many years before entering the soil as litterfall.